Journal of Operational Oceanography - Journal of Operational Oceanography (Taylor & Francis, 2026)
The Journal of Operational Oceanography will publish papers which examine the role of oceanography in contributing to the fields of: Numerical Weather Prediction
FI 0.41
Q4
Keywords: Engineering; Computing & Technology; Acuerdos transformativos; Transformative agreements; Oceanografía operacional; Pronóstico oceánico; Modelación oceánica; Observación oceánica